Transforming voluntary organisations for professional evaluation into central pillars of national evaluation systems - Tebogo Fish; Ayabulela Dlakavu; Matodzi Amisi; Steven Masvaure (African Evaluation Journal, 2022)
A study commissioned by the Centre for Learning on Evaluation and Results -Anglophone Africa (CLEAR-AA) and the African Evaluation Association (AfrEA) in 2021 highlights key strengths and challenges faced by African VOPEs in their quest to help strengthen NESs across the continent. Voluntary organisations for professional evaluation (VOPEs) have proliferated across the African continent, seeking to contribute to building effective national evaluation systems (NESs) that enhance development planning, implementation and appraisal.
A study commissioned by the Centre for Learning on Evaluation and Results -Anglophone Africa (CLEAR-AA) and the African Evaluation Association (AfrEA) in 2021 highlights key strengths and challenges faced by African VOPEs in their quest to help strengthen NESs across the continent. Voluntary organisations for professional evaluation (VOPEs) have proliferated across the African continent, seeking to contribute to building effective national evaluation systems (NESs) that enhance development planning, implementation and appraisal.